Efektivitas Undang-Undang Nomor 24 Tahun 2007 Tentang Penanggulangan Bencana dan Fikih Kebencanaan Terhadap Perilaku Warga Muhammadiyah (Studi Kasus Covid-19) - Isngadi, Isngadi; Khakim, Mufti (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
Disaster management is the obligation of the state in carrying out constitutional duties, namely protecting all spilled Indonesian blood. Disasters have the potential to cause casualties and property. Laws are needed as the basis for government decision making in disaster management. The effectiveness of implementing law number 24 of 2007 can be a benchmark for disaster management. The participation of civil society such as Muhammadiyah mass organizations is a supporting capacity in disaster management. This research is a normative study of the effectiveness of the law on disaster management and Muhammadiyah disaster management case study of Covid 19. The results of the research show that there are many things that need to be evaluated in the implementation of the implementation of the law.